Analisis Komparatif Efektivitas dan Strategi Blocking pada Middle Blocker, Opposite Hitter, dan Outside Hitter dalam Bolavoli - Marpaung, Deni Rahman; Purba, Dosipa; Sitorus, Joshua Jekson Very Alamsyah (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Blocking is one of the most decisive survival skills in modern volleyball because it directly influences rally outcomes and the tactical momentum of the game. Each player position, namely Middle Blocker (MB), Opposite Hitter (OPP), and Outside Hitter (OH), has different technical, tactical, and cognitive demands. However, previous research has tended to discuss blocking ability in general without considering positional differences. This study aims to systematically review recent literature to compare the effectiveness of blocking, tactical strategies, and performance determinants for the MB, OPP, and OH positions at the elite level. The systematic review method was conducted based on the PRISMA guidelines, with searches in five databases: Scopus, Web of Science, PubMed, SPORTDiscus, and Google Scholar, covering the period from 2015 to 2024. Analysis of the article reveals a clear hierarchy of positions. MB players have the highest block success rate, followed by OPP and OH. Success factors include reaction time, lateral agility, vertical jump ability, hand technique, and tactical intelligence. The analysis results show a clear hierarchy regarding block effectiveness, with MB players having the highest block success rate, followed by OPP and OH. Block success is influenced by several key factors, including reaction time, lateral agility, vertical jump ability, hand technique, and tactical intelligence in reading opponent attacks. It is concluded that the effectiveness of the block is position-specific, so training programs need to be designed differently according to each player's role.